Reducing 30-Day Rehospitalization Rates Using a Transition of Care Clinic Model in a Single Medical Center - Hudali, Tamer (Adv Med, 2017)
BACKGROUND: Rehospitalization for medical patients is common. Multiple interventions of varying complexity have been shown to be effective in achieving that goal with variable results in the literature. For medical patients discharged home, no single intervention implemented alone has been shown to have a sustainable effect in preventing rehospitalization. OBJECTIVE: To study the effect of a transition of care clinic model on the 30-day rehospitalization rate in a single medical center. METHODS: Retrospective observational analysis of adult patients discharged home from Memorial Medical Center from September 1, 2014, through December 31, 2014. The primary outcome was to compare hospital readmission rates between patients who followed up with a transition of care (TOC) clinic and those who did not. RESULTS: The study population included 378 patient discharges. A total of 40 patients (10.6%) were readmitted to the hospital within 30 days of discharge. Patients who attended the TOC clinic had a significantly lower 30-day readmission rates (3.8% versus 11.7%). A Cox regression analysis showed that the TOC clinic attendance had a significant negative predication for readmission (HR 0.186, 95% CI 0.038–0.898, P = 0.038). CONCLUSION: Adopting a TOC model after discharging medical patients has reduced the readmission rates in our study.